GRAMMATICAL ERRORS IN INDONESIAN-ENGLISH TRANSLATION - Muh. Basuni; Khusnul Khotimah (Pusat Pengembangan Bahasa IAIN Tulungagung, 2014)
Learning English as second language (ESL) or Foreign Language (EFL) may lead the students to make errors as done by fifth semester students of English Department of IAIN Tulungagung Academic Year 2013/2014 when they leaned Indonesian-English translation. The differences of grammatical system of both languages are the difficult thing for them in translating text. This study aims to identify and classify the types of grammatical errors, to find out the errors that affect the meaning and the frequency of errors in each type, to know the contribution of student’s first language to the errors. Research method applied was descriptive quantitative study. The instruments were document and test. Error analysis was used as method of analyzing data. The result showed that there are 347 errors appeared in students’ translation. They were errors of misformation (132 times), omission (108 times), addition (74 times) and misordering (33 times). From those errors, there are 211 errors that affect the meaning. They were omission (80 times), addition (57 times), misformation (46 times), and misordering (27 times). The errors made by students indicate that they are still confused to apply good grammar in their translation. Their translations are influenced by their first language interference.